Advances of herbivore-secreted elicitors and effectors in plant-insect interactions - Wang, Huiying; Shi, Shaojie; Hua, Wei (Frontiers in Plant Science, 2023)
Abstract Diverse molecular processes regulate the interactions between insect herbivores and their host plants. When exposed to insects, elicitors-induced plant defenses, a complex physiological and biochemical processes, will be produced, such as the activation of the jasmonic acid (JA) and salicylic acid (SA) pathways, Ca2+ flux, reactive oxygen species (ROS) burst, mitogen-activated protein kinase (MAPK) activation and other responses. For better adaptation, insects secrete a large number of effectors to interfere with the defenses at multiple levels. In plants, resistance (R) proteins have been evolved, which can recognize effectors and trigger stronger defense responses. However, only a few effectors recognized by R proteins have been identified till now. Multi-omics approaches for high-throughput elicitors/effectors identification and functional characterization have been developed. In this review, we mainly highlight the recent advances in identification of the elicitors, effectors secreted by insects, and their target proteins in plants and discuss their underlying molecular mechanisms, which will provide new inspiration for controlling these insect pests.